Estimation of Non-standard Employment of the Population - PRITVOROVA, Tatyana; KULOV, Olzhas; SYZDYKOVA, Elmira; GARTSUYEVA, Yekaterina; KIRDASINOVA, Kasiya; SHAMISHEVA, Nurgul (Journal of Advanced Research in Law and Economics, 2017)
The article is devoted to self-employment in Kazakhstan. The main groups of self-employment in Kazakhstan are covered. The issues of implementation of the programs ‘Road map of employment 2020’ and ‘Development of productive employment and mass entrepreneurship for 2017 - 2021 years’ are being studied. The analysis of independent employment in Kazakhstan on the basis of methodological researches is carried out. The features of development and self-employment phenomena in Kazakhstan are studied, and the problematic issues of this employment are indicated. The analysis of a sample study of self-employment was conducted in 2005-2016. The conclusions on the results of the employment survey on the number of employed people in general and the self-employed population of the country are summarized.